Rizal a holistic approach - Cabauatan, Wilfred F. (Mindshapers Co., Inc., 2016)
"This book intended to bring Rizal closer to the senses of Filipino srudents. Divided into nine brief yet richly woven chapters are the significant details on how he lived his life; what inspired him to write his novels and other rich literary masterpieces; and how his socio-political, educational and religious philosophies have impacted his fate."--Preface